THE INFLUENCE OF COMPETENCE WORK EXPERIENCE AND INFORMATION TECHNOLOGY UTILIZATION ON EMPLOYEE PERFORMANCE THROUGH WORK ETHICS OF EMPLOYEES OF FINANCIAL AND ASSET MANAGEMENT AGENCY IN KARIMUN REGENCY - Rieke Resty Afriany, Raden; Wibisono, Chablullah; Satriawan, Bambang; Khaddafi, Muammar (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
Every organization must be able to display excellent performance in various fields, especially those related to its stakeholders. The current increasingly complex environmental situation requires an organization to be able to satisfy the interests of various stakeholders. In this case, in addition to meeting the needs of its customers, the organization must also think about the interests of other parties such as shareholders, communities, governments, NGOs, financial institutions, educational institutions and so on, including the interests of its own employees. The purpose of this study was to analyze the effect of work experience, work competence, and the use of information technology on performance through work ethic as an intervening variable in all ASN of the Karimun Regency Regional Financial and Asset Management Agency totaling 104 respondents. Sampling in this study amounted to 104 samples. In this study, the sampling technique used was the census technique. The research method uses a quantitative approach with analysis of Partial Least Square (PLS) analysis techniques with the SmartPLS Version 4.0 program. The results of this study state that the work experience variable has a positive and significant effect on performance. Competency variables have a positive and insignificant effect on performance. Information technology utilization variable has a positive and insignificant effect on performance. The work ethic variable has a positive and significant effect on performance. The work experience variable has a positive and significant effect on work ethic. Work competency variable has a positive and significant effect on work ethic. Information technology placement variable has a positive and significant effect on work ethic. The work ethic variable is able to mediate the effect of work experience on performance. The work ethic variable is able to mediate the effect of work competence on performance. The work ethic variable is able to mediate the effect of the use of information technology on performance.